Entrepreneurship : an evidence-based guide - Baron, Robert A. (Edward Elgar, 2012)
"By presenting accurate knowledge about entrepreneurship itself, this book serves to convert the rising tide of interest in entrepreneurship into advice and guidance that can actually assist entrepreneurs in achieving their goals. In order to do so, this book presents evidence-based information concerning the factors that encourage entrepreneurship's emergence, including the conditions that shape its outcomes and how it unfolds as a process ... By combining evidence-based knowledge with the hard-earned wisdom of experienced entrepreneurs, this volume offers a balanced and inclusive guide useful to both current and aspiring entrepreneurs."--Back cover